Well Differentiated B3 Thymoma complicated with Vena Cava Superior Syndrome undergo Debulking and Chemotherapy - Semara Putra, Wayan Wahyu; Noor Chozin, Iin; Wantry, Kenty; Isharanto, Artono; Erawati, Rachma Dini (Malang Respiratory Journal, 2020)
Background: Thymoma is a rare neoplasm. This incident is comparable to 390 new cases reported per year. Genetic factors are believed to be one of the factors of B3 thymoma and thymus carcinoma. Multimodality of thymoma therapy (surgery, radiation and chemotherapy) gives better results.Case Report: Mr A, 29 years old, with initial diagnosis of stage IV thymoma (according to Masaoka) with SVKS then undergo debulking, followed by chemotherapy with a regimen of Cisplatin + Vincristin, Cyclophospamid, Doxorubicin, Prednison every 21 days as much as 6 times. Subjective responses indicated by reduced complaints of chest pain and loss of swelling of the right arm. Semisubjective response indicated by increase of body weight. Objective response is progressive, so can be continued with second line chemotherapy or radiotherapy.Conclusion: The prognosis of patient with well differentiated thymic carcinoma stadium iv (thymoma b3) complicated with vena cava superior syndrome was poor because of the objective response of the chemotherapy was progressive, and the relapse case was higher.